PERAN DIPLOMASI IMAN (FAITH DIPLOMACY) DALAM PENGUATAN REZIM PERLINDUNGAN PENGUNGSI DALAM HUKUM INTERNASIONAL - Rifa'i, Iman Jalaludin (Universitas Ibn Khaldun Bogor, 2025)
This study aims to analyze the role of Faith Diplomacy in strengthening the international refugee protection regime through the framework of international law. The research employs a normative legal approach using doctrinal, conceptual, and comparative analysis methods. The data are derived from international legal instruments, reports from international bodies such as UNHCR and OIC, and scholarly publications from 2020–2025. The findings indicate that faith diplomacy plays a strategic role in bridging the gap between positive legal norms and universal moral values, thereby enhancing the legitimacy and effectiveness of the implementation of non-refoulement, responsibility sharing, and respect for human dignity. Furthermore, faith diplomacy introduces a new paradigm in international law—a human-centered and ethical-normative approach—wherein legal norms gain both legal and moral legitimacy. Consequently, faith diplomacy serves as an ethical foundation for strengthening the global refugee protection regime toward greater inclusivity, adaptability, and justice.